The Effect of Supply Chain Management on Indonesian Pharmaceutical Industry - Roespinoedji, Djoko; Hadian, Niki; Saadah, Saadah; Damopolii, Veronika Listi Ferdini; Isa, Azizan Mohamed (International Journal of Supply Chain Management, 2019)
The objective of this research is to inspect the consequence of effective SCM in terms of delivery, after-sales services and responsiveness on customer retention along with the mediating role of customer relationship on the Indonesian Pharmaceutical company. 5point Likert scale is used to collect the data. Random sampling technique is used on the 200 respondents from Indonesian medical officers. PLS3 is used to analyze the data. The findings of this concluded aftersales services, deliveries and responsiveness have been positively significant associated to CR and also customer relationship positively influenced on C. retention. The study gives to fill the lack of investigation on the SCM service to the C. retention between general consultants from Indonesian private consulting room.